2017
DOI: 10.7717/peerj.3811
|View full text |Cite
|
Sign up to set email alerts
|

Fish Ontology framework for taxonomy-based fish recognition

Abstract: Life science ontologies play an important role in Semantic Web. Given the diversity in fish species and the associated wealth of information, it is imperative to develop an ontology capable of linking and integrating this information in an automated fashion. As such, we introduce the Fish Ontology (FO), an automated classification architecture of existing fish taxa which provides taxonomic information on unknown fish based on metadata restrictions. It is designed to support knowledge discovery, provide semanti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Harmonizing fish data annotation with an ontology will enable easier data aggregation and analysis. One available ontology, FISHO ( https://bioportal.bioontology.org/ontologies/FISHO ), 18 focuses on ichthyology, diversity, and adaptation. The Food and Agriculture Organization (FAO) of the United Nations initiated several fisheries ontologies, but the ontologies available remained drafts.…”
Section: Resultsmentioning
confidence: 99%
“…Harmonizing fish data annotation with an ontology will enable easier data aggregation and analysis. One available ontology, FISHO ( https://bioportal.bioontology.org/ontologies/FISHO ), 18 focuses on ichthyology, diversity, and adaptation. The Food and Agriculture Organization (FAO) of the United Nations initiated several fisheries ontologies, but the ontologies available remained drafts.…”
Section: Resultsmentioning
confidence: 99%
“…The fish ontology architecture (Ref. [57] p. 6), for example, provides links between the property "extinct", the property category "fish status", and the entity "fish".…”
Section: Ontologiesmentioning
confidence: 99%
“…They also reported that the returned accuracy by the trained personnel and experts for distinguishing and labelling specimens is expected to be in the range of 64 % to 95 %, which is within the performance range of automated methods. Classification of specimens' images to their corresponding species requires development of models and methods that are able to characterize a species' morphology and apply this knowledge to their recognition (Wong et al, 2016;Ali et al, 2017).…”
Section: Introductionmentioning
confidence: 99%